2021
DOI: 10.1039/d1bm00896j
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery to malignant brain tumors: potential biomaterial-based therapeutic/adjuvant strategies

Abstract: Glioblastoma (GBM) is the most aggressive malignant brain tumor and is associated with a very poor prognosis. The standard treatment for newly diagnosed patients involves total tumor surgical resection (if...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 145 publications
(187 reference statements)
0
17
0
Order By: Relevance
“…Analysis of the hydrogel sizes indicated that they swelled by approximately 112% of their original template size once removed from the template (Figure 3f). Local drug delivery as a strategy for therapeutic delivery to brain cancers would allow the administration of drugs that cannot pass the blood-brain barrier [32]. Local delivery therefore vastly increases the range of potential chemotherapeutic drugs that can be utilized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the hydrogel sizes indicated that they swelled by approximately 112% of their original template size once removed from the template (Figure 3f). Local drug delivery as a strategy for therapeutic delivery to brain cancers would allow the administration of drugs that cannot pass the blood-brain barrier [32]. Local delivery therefore vastly increases the range of potential chemotherapeutic drugs that can be utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Local drug delivery as a strategy for therapeutic delivery to brain cancers would allow the administration of drugs that cannot pass the blood–brain barrier [ 32 ]. Local delivery therefore vastly increases the range of potential chemotherapeutic drugs that can be utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with systemic medication, loading drugs in the internal sustained-release carrier of the implant can enable the slow release of the drugs into the microenvironment around the implant, which can not only reduce drug dosage and complications but also achieve better therapeutic effects [ 48 ]. Based on the above ideas, this study proposed a drug sustained-release system for osteoporosis treatment with Mg-MOF-74 as the drug carrier, and icariin was loaded to obtain ICA@MOF.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis occurs within approximately ∼2 cm of the tumor's original site, which means it is close to where the drugs were loaded locally; the administration of the drugs will no longer face the BBB limitations [249]. Different strategies for local delivery to improve the GBM survival rate have been developed, including intranasal drugs delivery, convection enhanced delivery, and direct injection of the drugs including rigid implants and hydrogels [250].…”
Section: Local Deliverymentioning
confidence: 99%